2018
DOI: 10.1515/rtuect-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Kinetic Parameters for the Thermal Decomposition of Parthenium hysterophorus

Abstract: A kinetic study of pyrolysis process of Parthenium hysterophorous is carried out by using thermogravimetric analysis (TGA) equipment. The present study investigates the thermal degradation and determination of the kinetic parameters such as activation E and the frequency factor A using model-free methods given by Flynn Wall and Ozawa (FWO), Kissinger-Akahira-Sonuse (KAS) and Kissinger, and model-fitting (Coats Redfern). The results derived from thermal decomposition process demarcate decomposition of Partheniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 36 publications
(40 reference statements)
1
37
0
Order By: Relevance
“…It is suggested that the kinetic analysis should not be based on the single heating rate [8,11]. Furthermore, thermal decomposition of weed indicates that the results obtained from Coats-Redfern are highly incoherent as compared to model-free scheme [12]. However, this method can be transformed into iso-conversional method through rearrangement of the conventional form of Coats-Redfern equation (1) [8].…”
Section: Chemical Kineticsmentioning
confidence: 99%
“…It is suggested that the kinetic analysis should not be based on the single heating rate [8,11]. Furthermore, thermal decomposition of weed indicates that the results obtained from Coats-Redfern are highly incoherent as compared to model-free scheme [12]. However, this method can be transformed into iso-conversional method through rearrangement of the conventional form of Coats-Redfern equation (1) [8].…”
Section: Chemical Kineticsmentioning
confidence: 99%
“…Thus, it can be concluded that the predicted solution converges if the mathematical model involves the nonlinear thermal profile. The results obtained for pine needles are compared with similar kind of coniferous species, and it has been found that activation energy is within the range of activation energy derived from other statistical models [14,[68][69][70][71][72][73].…”
Section: Resultsmentioning
confidence: 68%
“…formation and growth of nuclei. Detailed information about kinetic models of solid decomposition is reported in the literature [14][15][16]. When a solid sample undergoes thermal treatment, the amplitudes of the vibration of the lattice increase proportionally with temperature, which finally allows physical as well as chemical transformation of sample.…”
Section: Thermal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The actual process of the pyrolysis or lack thereof is dependent on the different densities, and the temperature of the given point in the system. The latter is defined by mid-products, and different behaviour [39,40], this is why there are regulations in place for the level of chipping for chipped biomass (whether we're talking about combustion or pyrolysis). By chipping the biomass, the size of pieces reduces, but the entire surface area of the chips increases.…”
Section: Introductionmentioning
confidence: 99%